Fighting Nutrition and Health Misinformation: Enlisting the Public's Help. Issue 1 (January 2022) - Rowe, Sylvia; Alexander, Nick
Abstract : The twin phenomena of scientific misinformation and disinformation have recently been the object of an intense discussion among communicators of nutrition, health, and other science information. Especially with the rapidly evolving social media ecosystem, issues of public trust in consensus science have increasingly concerned those professionals whose mission it is to convey truthful and credible information. For several years, the National Academies of Sciences, Engineering, and Medicine have been studying the "Science of Science Communication" and other aspects of public credulity in scientific findings, and recently, the National Academy of Medicine published a discussion article proposing strategies for combatting the spread of health misinformation—including the creation of source-vetting guidance to be enacted by the major social media platforms. In the present article, the authors, who for years have explored issues around public trust and new media communication of science, explore the Academy's proposals and offer their own guidance on reconciling public perceptions with "authoritative" health and other science communications.